How to Establish Relationship & Trust with Documentary Participant - Ainren Azren, Mustafa Bakri; Jachel Sze Zhi, Loh; Ismail Gillian, Anne; Chong Lee, Yow (Mini Film Festival, 2022)
Infographics on "How to Establish Relationship & Trust with Documentary Participant". The content is extracted from MFF Doc Workshop (1) presented by Ms. Cheyenne Tan, designed by Ainren, Jachel and Ismail, advised and edited by Yow.